2021
DOI: 10.1126/sciadv.abf6063
|View full text |Cite
|
Sign up to set email alerts
|

An EMT–primary cilium–GLIS2 signaling axis regulates mammogenesis and claudin-low breast tumorigenesis

Abstract: The epithelial-mesenchymal transition (EMT) and primary ciliogenesis induce stem cell properties in basal mammary stem cells (MaSCs) to promote mammogenesis, but the underlying mechanisms remain incompletely understood. Here, we show that EMT transcription factors promote ciliogenesis upon entry into intermediate EMT states by activating ciliogenesis inducers, including FGFR1. The resulting primary cilia promote ubiquitination and inactivation of a transcriptional repressor, GLIS2, which localizes to the cilia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…However, GLIS2 does not contain a consensus CLS sequence suggesting that its ciliary localization might be mediated by a different mechanism. Regulation of GLIS2 transcriptional activity by primary cilium-associated mechanisms is discussed below in more detail [ 11 , 44 ].…”
Section: Glis Proteins and Primary Ciliummentioning
confidence: 99%
See 3 more Smart Citations
“…However, GLIS2 does not contain a consensus CLS sequence suggesting that its ciliary localization might be mediated by a different mechanism. Regulation of GLIS2 transcriptional activity by primary cilium-associated mechanisms is discussed below in more detail [ 11 , 44 ].…”
Section: Glis Proteins and Primary Ciliummentioning
confidence: 99%
“…The transcriptional activation by GLIS1-3 is mediated by the recruitment of co-activators, such as EP300/p300, to the transactivation domain (TAD) at their carboxy-terminus ( Figure 1 ). Although GLIS2 can activate gene transcription, in several cell types it appears to function largely as a repressor [ 3 , 5 , 8 , 10 , 11 , 12 , 13 ]. GLIS2 repressor function is, in part, mediated through its recruitment of the co-repressor, C-terminal binding protein 1 (CTBP1) [ 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutathione peroxidase 1 (GPX1) is a vital antioxidant enzyme that can catabolize the hydrogen oxide entering the human body and reduce peroxide's damage to the body (Huang et al, 2018). As one of the important cell biology processes, epithelial-mesenchymal transition (EMT) plays a key role in multiple links of tumor metastasis (Wilson et al, 2021;Yang et al, 2021). A previous study also revealed that GPX1 inhibits EMT progression in cancer and plays an anticancer role (Meng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%